Methylprednisolone 100 mg Tablet Formulation With Pea Protein: Experimental Approaches Over Intestinal Permeability and Cytotoxicity - Koç, Erhan; Çiftçi, Fatih; Çalık, Hilal; Korkmaz, Seval; Koç, Rabia Çakır (Taylor & Francis, 2023)
Objective: This study was carried out to transform the hydrolyzed pea protein into a pharmaceutical tablet form by masking methylprednisolone. Significance: This study provides some crucial contributions in showing how functional excipients such as pea protein, which are generally used in food industries, can be used in pharmaceutical product formulations and their effects. Methods: Methylprednisolone was formulated using spray drying technology. Design Expert Software (Version 13) was used for the statistical analysis. The in vitro cytotoxic effects for NIH/3T3 mouse fibroblast cells were investigated by XTT cell viability assay. HPLC was used to analyze the Caco-2 permeability studies and dissolution tests. Results: The optimum formulation was evaluated against the reference product by performing cytotoxicity and cell permeability studies. According to our test results, Papp (apparent permeability) values of Methylprednisolone were measured around 3 10-6 cm/s and Fa (fraction absorbed) values around 30%. These data indicate that Methylprednisolone HCl has ‘moderate permeability’ and our study confirmed that it could have belonged to BCS Class II-IV since both low solubility and moderate permeability. Conclusion: The findings offer valuable information to guide and inform the use of pea protein in pharmaceutical formulations. Significant effects on methylprednisolone tablet formulation designed with the philosophy of quality by design (QbD) of pea protein have been demonstrated by both in vitro and cell studies.
Keywords: Methylprednisolone; DoE; Quality by Design; Formulation; Spray Dry; Factorial Design; Caco-2; Cytotoxicity